Development of Creative Tourism Village in West Bandung Regency with Regional Innovation Capacity Concept - Ari Ana Fatmawati; Sugeng Santoso (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose of this study is to develop a creative tourism village model based on Regional Innovation Capacity which is expected to contribute to the development and management of tourism village policies. Methods: The Methode of this research is Regional Innovation Capacity (KID) that was developed from the theory of National Innovation Capacity (KIN). The survey was conducted on respondents consisting of policy makers, tourist attraction managers, partner managers, visitors, and creative economy actors. Data processing is done by exponential regression. The innovation-based creative tourism village model developed with KID as the Y variable and the X variable which consists of 37 variables, namely 15 Innovation Public Infrastructure variables, 17 Industrial Cluster variables, and 5 Public Infrastructure Relations between Innovation and Industrial Clusters variables. Finding/Results: The results of partial exponential regression processing with a significance of 5% indicate that: (i) KID will increase e^.386 = 1.47 on the X1.3 variable (Process of socializing the financing mechanism for Intellectual Property / Communal Intellectual Property / (Geographical Indications) ) in Kabupaten West Bandung) because the proportion of changes in X1.7 is 38.6%; (ii) KID will increase e^.362 = 1.43 in the X2.12 variable (Financing Services (Banks, Venture Capital, Crowd Funding, Sharia Financing) for business/industrial goods and services that can be utilized in Innovative Villages in the West Regency Bandung) because the proportion of changes in X2.12 is 36.2%.